2012
DOI: 10.1371/journal.pone.0040604
|View full text |Cite
|
Sign up to set email alerts
|

Early Brain Vulnerability in Wolfram Syndrome

Abstract: Wolfram Syndrome (WFS) is a rare autosomal recessive disease characterized by insulin-dependent diabetes mellitus, optic nerve atrophy, diabetes insipidus, deafness, and neurological dysfunction leading to death in mid-adulthood. WFS is caused by mutations in the WFS1 gene, which lead to endoplasmic reticulum (ER) stress-mediated cell death. Case studies have found widespread brain atrophy in late stage WFS. However, it is not known when in the disease course these brain abnormalities arise, and whether there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
106
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(115 citation statements)
references
References 93 publications
7
106
1
1
Order By: Relevance
“…However, patients also suffer from neuronal manifestations. MRI scans of Wolfram syndrome patients showed atrophy in brain tissue implying neurodegeneration in patients (7,10). To investigate the mechanisms of neurodegeneration in Wolfram syndrome human cells, we established Wolfram syndrome iPSC-derived neural progenitor lines and confirmed the observations found in rodent cells and animal models of Wolfram syndrome.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…However, patients also suffer from neuronal manifestations. MRI scans of Wolfram syndrome patients showed atrophy in brain tissue implying neurodegeneration in patients (7,10). To investigate the mechanisms of neurodegeneration in Wolfram syndrome human cells, we established Wolfram syndrome iPSC-derived neural progenitor lines and confirmed the observations found in rodent cells and animal models of Wolfram syndrome.…”
Section: Discussionmentioning
confidence: 64%
“…Insulin-dependent diabetes usually occurs as the initial manifestation during the first decade of life, whereas the diagnosis of Wolfram syndrome is invariably later, with onset of symptoms in the second and ensuing decades (7,10,11). Two causative genes for this genetic disorder have been identified and named Wolfram syndrome 1 (WFS1) and Wolfram syndrome 2 (WFS2) (12,13).…”
mentioning
confidence: 99%
“…Analogously, MRI in young, minimally affected patients in our study group revealed substantially subnormal brainstem volumes. 14,22 Assessment of children who test positive for the WFS gene mutation combined with longitudinal follow-up will be critical for sorting out these possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it is incurable and leads to a premature death at an average age of 35 years (2). Despite initial success with spectroscopybased studies (3), there is a lack of repeatable and robust markers for monitoring the clinical course of WFS. The aim of our study was to evaluate retinal parameters, measured with optical coherence tomography, as biomarkers of WFS progression.…”
mentioning
confidence: 99%